Improving Employee Mental Health: A Health Facility-Based Study in the United States - Gwain, Gerald Chia; Amu, Hubert; Bain, Luchuo Engelbert (Frontiers in Public Health, 2022)
Background: In the US, over 52.9 (21%) million adults lived with a mental health illness in 2020, with depression, being one of the commonest of these conditions. The World Health Organization ranks depression as the most important contributor to global disability. As frontline workers who are responsible for taking care of a myriad of patients daily, health workers are usually exposed to depressive situations which eventually result in the development of the condition among them. This study, therefore, developed an intervention to reduce depression among workers at the Outpatient Mental Health Clinic in Washington District of Columbia, United States. Methods: A pre-intervention survey was conducted among 43 employees. The survey used the already validated Patient Health Questionnaire depression scale (PHQ-9) to determine the prevalence of depression. The WHO Healthy Workplace Model was adopted in designing an instrument for the workplace determinants of depression. An mHealth intervention was then developed and implemented among the workers. After this, a post-intervention survey was conducted among the cohort. Descriptive and inferential statistics were adopted in analysing the data with STATA. Results: The pre-intervention survey showed a depression prevalence of 30.2% among the employees. The post-intervention survey, however, showed that the prevalence of depression among the employees reduced to 12.6%. The surveys also showed that the majority of employees who felt exposed to workplace hazards including harmful chemicals, expressed feelings of depression (pre-intervention=53.6%; post-intervention=80%). Conclusion: The intervention designed for this study was effective in reducing self-reported depression among employees. Improving employee mental health in health care facilities will require awareness raising among employees, mental health friendly policies, and regular follow up of employee mental health needs. Though this intervention was on a small scale, it shows promise for using cheap mhealth solutions in improving mental health at the work place.